Potential of nutraceutical products for irritable bowel syndrome remission maintenance - A. I. Ulyanin; Ye. A. Poluektova; Ch. S. Pavlov; V. T. Ivashkin (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
Aim of review. To summarize the modern data on pathogenesis of symptoms irritable bowel syndrome (IBS) symptoms, to present nutraceutical product «Standart zdorovya: GASTRO» as an agent for IBS remission maintenance. Summary. Recent data indicate essential changes of intestinal microbiota in IBS in comparison to healthy population. These changes may be associated to development of inflammatory processes of intestinal wall. Long-term inflammation may result in nociceptor hypersensitivity i.e. peripheral sensitization that in turn, lead to the central sensitization and indirectly - to gastrointestinal tract (GIT) motility disorders. Besides, change of intestinal microbiota may impact the development of emotional disorders (e.g.: impaired capacity of affected intestinal microbiota to produce neurotransmitters). Therefore, according to the results of available studies, intestinal microbiota changes in IBS is a key factor for the cascade of events including intestinal wall inflammation, changes of gastrointestinal motility, decreased threshold of gastrointestinal receptor sensitivity, as well as emotional disorders resulting in development of disease symptoms. Medical preparation for IBS remission induction and remission maintenance should possess probiotic/prebiotic and anti-inflammatory properties, reduce visceral sensitivity, normalize intestinal motility and modulate patients’ emotional sphere. Due to capacity of «Standart zdorovya: GASTRO» components to deliver above-listed effects it can be promising for administration in patients with IBS.